Atezolizumab and bevacizumab in patients with advanced hepatocellular carcinoma with impaired liver function and prior systemic therapy: a real-world experience. (February 2022) - de Castro, Tiago; Jochheim, Leonie S.; Bathon, Melanie; Welland, Sabrina; Scheiner, Bernhard; Shmanko, Kateryna; Roessler, Daniel; Ben Khaled, Najib; Jeschke, Matthias; Ludwig, Johannes M.; Marquardt, Jens U.; Weinmann, Arndt; et al.
Objective: Evaluation of the efficacy and safety of atezolizumab/bevacizumab in a real-world HCC cohort, including patients with impaired liver function and prior systemic therapy. Methods: Retrospective analysis of 147 HCC patients treated with atezolizumab/bevacizumab at six sites in Germany and Austria. Results: The overall response rate and disease control rate were 20.4% and 51.7%, respectively. Seventy-three patients (49.7%) met at least one major exclusion criterion of the IMbrave150 trial (IMbrave-OUT), whereas 74 patients (50.3%) were eligible (IMbrave-IN). Median overall survival (mOS) as well as median progression-free survival (mPFS) was significantly longer in IMbrave-IN versus IMbrave-OUT patients [mOS: 15.0 months (95% confidence interval (CI): 10.7–19.3] versus 6.0 months (95% CI: 3.2–8.9; p < 0.001) and mPFS: 8.7 months (95% CI: 5.9–11.5) versus 3.7 months (95% CI: 2.7–4.7; p < 0.001)]. Prior systemic treatment did not significantly affect mOS [hazard ratio (HR): 1.32 (95% CI: 0.78–2.23; p = 0.305)]. mOS according to ALBI grades 1/2/3 were 15.0 months (95% CI: not estimable), 8.6 months (95% CI: 5.4–11.7), and 3.2 months (95% CI: 0.3–6.1), respectively. ALBI grade and ECOG score were identified as independent prognostic factors [ALBI grade 2 versus 1; HR: 2.40 (95% CI: 1.34 – 4.30; p = 0.003), ALBI grade 3 versus 1; HR: 7.28 (95% CI: 3.30–16.08; p < 0.001), and ECOG ⩾2 versus 0; HR: 2.09 (95% CI: 1.03 – 4.23; p = 0.042)], respectively. Sixty-seven patients (45.6%) experienced an adverse event classified as CTCAE grade ⩾3. Patients in the IMbrave-OUT group were at increased risk of hepatic decompensation with encephalopathy (13.7% versus 1.4%, p = 0.004) and/or ascites (39.7% versus 9.5%; p < 0.001). Conclusion: In this real-world cohort, efficacy was comparable to the results of the IMbrave150 study and not affected by prior systemic treatment. ALBI grade and ECOG score were independently associated with survival. IMbrave-OUT patients were more likely to experience hepatic decompensation.